Cardiac Findings in Pediatric Patients With Multisystem Inflammatory Syndrome in Children Associated With COVID-19. (February 2021) - Minocha, Prashant K.; Phoon, Colin K. L.; Verma, Sourabh; Singh, Rakesh K.
Background: The overall severity of cardiac disease secondary to acute SARS-CoV-2 (severe acute respiratory syndrome coronavirus-2) infection in children appears to be much lower when compared with adults. However, the newly described multisystem inflammatory syndrome in children (MIS-C) associated with coronavirus disease 2019 (COVID-19) has been associated with cardiac complications. Methods: We reviewed the clinical course and cardiac testing results in pediatric patients hospitalized with MIS-C at 2 large hospital systems in the New York City metropolitan area over a 3-month period. Results: Of the 33 patients (median age 2.8 years) in the study cohort, 24 (73%) had at least one abnormality in cardiac testing: abnormal electrocardiogram (48%), elevated brain natriuretic peptide (43%), abnormal echocardiogram (30%), and/or elevated troponin (21%). Electrocardiogram and echocardiogram abnormalities all resolved by the 2-week outpatient follow-up cardiology visit. Conclusion: While 73% of pediatric patients with MIS-C had evidence of abnormal cardiac testing on hospital admission in our study, all cardiac testing was normal by outpatient hospital discharge follow-up. Cardiac screening tests should be performed in all patients diagnosed with MIS-C given the high rate of abnormal cardiac findings in our study cohort.